Stages of Grief as Cultural Narratives: Understanding Maternal Loss Through Qualitative Content Analysis - Zerlinda Christine Aldira Sanam (PT. Intelek Cendikiawan Nusantara, 2026)
Women’s experiences of grief are complex emotional processes shaped by relational and cultural contexts as well as by the ways such experiences are narrated. This study explores the representation of grief stages in narratives of mothers who lost their children as depicted in the memoir Kisah Sejati Ibu yang Kehilangan Buah Hati by Xin Ran. Using a qualitative content analysis approach, the study applied a deductive framework based on Kübler-Ross’s stages of grief to identify narrative expressions related to denial, anger, bargaining, depression, and acceptance. Data were obtained through intensive and repeated readings of the text, focusing on meaningful narrative units that reflected emotional responses to loss. The findings indicate that grief stages were not represented linearly across narratives. Depression emerged as the most consistent and dominant stage, followed by denial, bargaining, and acceptance, while anger was absent. Additional themes of ongoing efforts to reunite with the child and expressions of hope were also identified. These results suggest that maternal grief is subjectively constructed and influenced by sociocultural norms that shape emotional expression within narrative contexts. The study highlights the importance of understanding grief models as interpretative frameworks rather than fixed emotional sequences, particularly when analyzing culturally embedded narratives.